Kinase Inhibitors as Potential Therapeutic Agents in the Treatment of COVID-19 - Naik, Rajashri R.; Shakya, Ashok K.; Aladwan, Safwan M.; El-Tanani, Mohamed (Frontiers in Pharmacology, 2022)
Corona virus first appeared in the Wuhan Province of China and later spread rapidly all over the world. To further control the spread of the virus, the aim of therapeutic strategy is to target the life cycle of the virus, control the respiratory distress and reduce the severe symptoms associated with it, that may be life threatening. Several kinase inhibitors have exhibited antiviral activity against various viruses like MERS, SARS-CoV-1 and have been used against SARS-CoV-2 as these kinase inhibitors exhibited their potential therapeutic effects. There are several FDA-approved kinase inhibitors that block the viral life cycle and the inflammatory response. Repurposing these kinase inhibitors will be a realistic alternative because they have previously undergone safety testing and are readily available for clinical trials and treatment. In the present paper we are highlighting the approved kinase inhibitors that have the antiviral potential to suppress the life cycle of the virus from entry to the spread of the virus in the host cell. We have also emphasized on the inhibitors that suppressed the inflammatory response associated with the corona viral infection.